The relationship between school, health and legislation for the achievement of an anti-tobacco education - Llopiz Guerra, Karel (2021)
Faced with adverse circumstances, many people have sought refuge in drug addictions, drug use and abuse, which have negative consequences for their health. The authorities and professionals of different countries have developed a group of actions in the educational, legal, social and environmental fields, and have declared a very marked fight for the prevention of legal drugs. The aim of this article is to characterize the intersectoral link on smoking and its education, attenuation and control based on a study of the situation in the contemporary world.